2016
DOI: 10.1139/cjpp-2015-0316
|View full text |Cite
|
Sign up to set email alerts
|

The hydrogen sulfide releasing compounds ATB-346 and diallyl trisulfide attenuate streptozotocin-induced cognitive impairment, neuroinflammation, and oxidative stress in rats: involvement of asymmetric dimethylarginine

Abstract: Hydrogen sulfide (H2S) has attracted interest as a gaseous mediator involved in diverse processes in the nervous system, particularly with respect to learning and memory. However, its therapeutic potential in Alzheimer disease (AD) is not fully explored. Therefore, the effects of H2S-releasing compounds against AD-like behavioural and biochemical abnormalities were investigated. Memory deficit was induced by intracerberoventicular injection of streptozotocin (STZ, 3 mg·kg(-1)). Animals were randomly assigned i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…Diallyl trisulfide also protects motor neurons and mediates cell survival by enhancing autophagy and stimulating antioxidant enzymes [56]. Additionally, Mostafa [57] reported that DAT protected neurons and improved cognitive functions in streptozotocin-induced diabetic rats through H 2 S release. In addition, Allium sativum was found to significantly decrease the expression of caspase-3 pro-apoptotic protein marker and up-regulate the anti-apoptotic genes because it contains many sulfur-containing compounds and volatile oil [58].…”
Section: Discussionmentioning
confidence: 99%
“…Diallyl trisulfide also protects motor neurons and mediates cell survival by enhancing autophagy and stimulating antioxidant enzymes [56]. Additionally, Mostafa [57] reported that DAT protected neurons and improved cognitive functions in streptozotocin-induced diabetic rats through H 2 S release. In addition, Allium sativum was found to significantly decrease the expression of caspase-3 pro-apoptotic protein marker and up-regulate the anti-apoptotic genes because it contains many sulfur-containing compounds and volatile oil [58].…”
Section: Discussionmentioning
confidence: 99%
“…In rat primary hepatocytes, DATS could enhance antioxidation and detoxification capabilities by increasing the intracellular GSH level and the activity of glutathione peroxidase, glutathione reductase, or glutathione S-transferase (Wu et al 2004 ). DATS reduced levels of malondialdehyde, asymmetric dimethylarginine, and acetylcholinestrase activity, while increasing GSH levels (Mostafa et al 2016 ). DATS inhibited oxidative stress and apoptosis in an ethanol-induced model (Chen et al 2016 ), and had a protective effect against arsenic-induced oxidative stress in rat erythrocytes and lymphocytes (Prabu and Sumedha 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diallyl trisulfide demonstrates antioxidative effects, which are associated with the changes in the activity of antioxidant enzymes and the level of glutathione (Wu et al 2004 ; Zhang et al 2016 ; Zeng et al 2008 ; Mostafa et al 2016 ; Prabu and Sumedha 2014 ; Hu et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additional experimental models where ATB-346 exerted beneficial effects include a mouse model of spinal cord injury (Campolo et al, 2013); a mouse model of traumatic brain injury (Campolo et al, 2014); a rat model of stress ulcers (Fomenko et al, 2014); a rat model of nonerosive esophagitis (Khyrivska et al, 2014); a rat model of ligature-induced periodontitis (Herrera et al, 2015); two different mouse models of intestinal carcinogenesis (Elsheikh et al, 2014;Paul-Clark et al, 2016); and a streptozotocin-induced cognitive impairment, neuroinflammation, and oxidative stress model in rats (Mostafa et al, 2016). In addition, at higher concentrations (100 mM) in vitro, ATB-346 induced melanoma cell apoptosis, whereas at a dose of [43 (mmol/kg)/day)] in vivo, ATB-346 significantly reduced melanoma development in vivo in tumor-bearing mice (De Cicco et al, 2016).…”
Section: Combined (Or Hybrid) Molecules: H 2 S-donating Derivamentioning
confidence: 99%